Proteomic analysis of cytochromes P450: a mass spectrometry approach. (25th October 2006) - Wang, Y.; Al-Gazzar, A.; Seibert, C.; Sharif, A.; Lane, C.; Griffiths, W.J.
Abstract : In human, the CYP (cytochrome P450) superfamily comprises 57 genes arranged in 18 families and 42 subfamiles. These genes encode for enzymes involved in the metabolism of drugs, foreign chemicals, fatty acids, eicosanoids and cholesterol. Additionally, they play roles in bile acid biosynthesis, steroid synthesis and metabolism, and vitamin D3 synthesis and metabolism. Mutations in many CYP genes cause inborn errors of metabolism and contribute to increased risk of cancer. MS provides a convenient method for the identification and quantification of CYP enzymes, and in the present paper we will review the current state of the technology for such an analysis.